Нові дослідження Тельманівського могильника у м. Луганськ - Красильніков, К.І.; Апарєєв, С.М.; Пробийголова, О.С. (Археологія, 2007)
Розглянуто матеріали рятувальних розкопок ґрунтового могильника біля м. Луганськ, подано відомості про поховання доби бронзи. В статье обобщены результаты спасательных работ могильника, возникшего на естественном всхолмлении в долине
р. Ольховая в черте г. Луганск. Раскопками вскрыт участок (75 м²), на котором компактно на площади 30 м² выявено 8 захоронений (3 — катакомбных, 4 — срубных, 1 — средневековое (?)). Катакомбные погребения датируются
XVII—XVI cт. до н. э. и относятся к донецким и бахмутско-манычским древностям. Погребения поздней бронзы
определяются по устройству погребальных ям, позам умерших и керамике. The authors of the article summarize the results of archaeological rescue work in burial ground situated on the hill in the
valley of the Olkhova River within the borders of Lugansk. The excavations covered the territory of 75 sq. m, of which 30
sq. m was a compact area for 8 graves (3 are of Catacomb culture, 4 of Zrubna culture, and 1 of Mediaeval Age (?)). The
graves of Catacomb culture dating from the 17th—16th cc. BC belong to Donetsk and Bakhmutka-Manych antiquities. The
tombs of Late Bronze Age are defined by the arrangement of burial pits, poses of the dead, and ceramics.